The Study of Antiangiogenic Effects of Oxovanadium(IV) Complex of N,N'-Dipyridoxyl(1,2-cyclopropanediamine) Schiff Base on the Chorioallantoic Membrane of Chick Embryos Cells - Parisa Ghorbani; S. Ali Beyramabadi; Masoud Homayouni-Tabrizi; Parichehreh Yaghmaei (Fasa University of Medical Sciences, 2019)
Background & Objective: Schiff bases are considered as an important group of compounds in the development of new drugs. The current approach to finding more effective treatment for cancer is to set up different stages of the angiogenesis process using angiogenesis suppressors, such as metal complexes synthesized from the Schiff bases. Therefore, the aim of this research was to investigate the antiangiogenic effects of oxovanadium(IV) complex of N,N'-dipyridoxyl(1,2-cyclopropanediamine) Schiff base on the chorioallantoic membrane of chick embryos cells. Materials & methods: Anti-angiogenic activity of oxovanadium(IV) complex of N,N'-dipyridoxyl(1,2-cyclopropanediamine) Schiff base was evaluated using Real-time PCR technique to evaluate the expression changes in angiogenesis-related genes in MCF-7 breast cancer cells and CAM test. Results: The study of alterations in the expression of genes showed that oxovanadium(IV) complex of N,N'-dipyridoxyl(1,2-cyclopropanediamine) Schiff base had a significant inhibitory effect on the expression of both genes involved in angiogenesis. The findings of the CAM test showed that there was a significant decrease in the number and length of the vessels treated with different doses of the complex (100, 200, 400 and 800 μg/mL) (P <0.01 and P <0.001). Also, there was a significant decrease in weight and height of embryos treated with complex compared to control group at P <0.05, P <0.01 and P <0.001. Conclusion: In this study, the oxovanadium(IV) complex of N,N'-dipyridoxyl(1,2-cyclopropanediamine) Schiff base has antiangiogenesis effects that make the use of this complex possible for cancer treatment.